Pro Linux high availability clustering - Vugt, Sander van (Expert's voice in Linux., 2014)
This book explains essential high-availability clustering components on all Linux platforms, giving the reader insight into building solutions for any specific case needed. Topics covered include: configuring Apache for high availability, creating an Open Source SAN based on DRBD, iSCSI and HA clustering; setting up a load-balanced Web server cluster with a back-end, highly-available database; setting up a KVM virtualization platform with high-availability protection for a virtual machine; designing Linux high availability clusters; setting up an environment to protect mission critical applications; connecting servers in a redundant way to the SAN; creating an affordable SAN based on open source software; seting up clusters for protection of Oracle and SAP workloads; writing cluster resource script; creating an open source SAN and a free hypervisor using KVM as the virtualization platform; and setting up a versatile, fault-tolerant, high-performance Web shop. --